MR Imaging Study of Edema-like Change along the Optic Tract in Patients with Pituitary Region Tumors - Saeki, Naokatsu; Uchino, Yoshio; Murai, Hisayuki; Kubota, Motoo; Isobe, Kouichi; Uno, Takashi; Sunami, Kenro; Yamaura, Akira (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Edema-like change along the optic tract commonly occurs in association with craniopharyngiomas. The aim of this study was to clarify whether it occurs in association with other common pituitary region tumors and to elucidate its mechanism as seen on MR images.METHODS: Fifty patients with pituitary region tumors that were touching or compressing the optic pathway underwent heavily T2-weighted MR imaging before and after treatment.RESULTS: Edema-like change along the optic tract was visible on the images of four of 25 pituitary adenomas, eight of 11 craniopharyngiomas, one germ cell tumor, and one malignant lymphoma and was not visible on the images of seven meningiomas and five Rathke’s cleft cysts. After therapeutic decompression of the optic pathway, the edema-like change disappeared and large Virchow-Robin spaces, present under normal conditions, became visible along the optic tract. Comparison of pre- and post-treatment coronal and axial view MR images revealed that the edema-like change had been located at, along, and/or around the large Virchow-Robin spaces along the optic tract.CONCLUSION: Edema-like change occurs in association with pituitary region tumors other than craniopharyngiomas. It is related with distension of normally present large Virchow-Robin spaces adjacent to the optic tract. Because Virchow-Robin spaces are speculated to be a drainage route of interstitial fluid into the subarachnoid space, their distension may be related to the fluid retention in and along the Virchow-Robin spaces, the outlet of which into the subpial and/or subarachnoid space(s) is blocked by pituitary region tumors.